Perbandingan Pendapatan Nelayan Pekerja dengan Standar Upah Minimum Regional (UMR) Kabupaten Kulon Progo - Catur Pramono Adi; Dian Sutono HS (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2018)
This research wa aimed to know the implementation of profit share system and wage system that are applied on gill net fishery business at Trisik Beach, Kulon Progo Regency. It was to know BEP level that is considered as limitation in determining the implementation of profit share system and to compare between wage system and profit share system that is earned by fisherman and ship’s owner with the UMR on Yogyakarta The reseach was conducted on Trisik Beach, banaran, Galur Sub district, Kulon Progo Regency in the early of August until the early of November 2017. The method that were used in this research included case study method, drawing sample, data collecting and data analyzing. The result of this reseach showed that ship’s crew earned Rp.2.284.000,- per mount and Rp.10.420,- per hour, ship’s captain earned Rp.6.602.000,- per month and Rp.300.420,- per hour. But for the company staf, they earned Rp.1.144.812,- per month and Rp. 38.160,- per day and also Rp.4.770,- per hour. By those way, it was more profitable using profit share system on Gill Net Monofilament Fihery business at Trisik Beach, Kulon Progo Regency compare to UMR 2017 at that Region, is Rp.1.373.600,–